TOPENG SEBAGAI INSPIRASI DALAM KARYA SENI GRAFIS DENGAN TEKNIK RELIEF PRINT - M. HADI PUTRA, Dr. Budiwirman, M.Pd. Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2017)
Mask has its own charm, has a variety of unique types and shapes, each mask also has a variety of characteristics that reflect the nature of humans. The purpose of lifting about masks is through artwork, artists can convey messages and goals to be conveyed, because artwork is the language of an artist. Likewise with the author, through the final task entitled,